2010
DOI: 10.1073/pnas.0911857107
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic O-GlcNAc cycling at promoters of Caenorhabditis elegans genes regulating longevity, stress, and immunity

Abstract: Nutrient-driven O-GlcNAcylation of key components of the transcription machinery may epigenetically modulate gene expression in metazoans. The global effects of GlcNAcylation on transcription can be addressed directly in C. elegans because knockouts of the O-GlcNAc cycling enzymes are viable and fertile. Using anti-O-GlcNAc ChIP-on-chip whole-genome tiling arrays on wild-type and mutant strains, we detected over 800 promoters where O-GlcNAc cycling occurs, including microRNA loci and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
164
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 69 publications
11
164
1
Order By: Relevance
“…Because UDP-GlcNAc is a nutrient sensor (6), the identification of an O-GlcNAc sites on histones may lead to new insights regarding how nutritional intake directly affects transcriptional activity of metabolic genes (50,51). Indeed, studies using ChIP sequencing have revealed that O-GlcNAcylated chromatin-associated proteins regulate transcription of metabolic and aging-related genes (52). The identification of H3T32Glc provides a specific epigenetic marker for future studies in insulin signaling and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Because UDP-GlcNAc is a nutrient sensor (6), the identification of an O-GlcNAc sites on histones may lead to new insights regarding how nutritional intake directly affects transcriptional activity of metabolic genes (50,51). Indeed, studies using ChIP sequencing have revealed that O-GlcNAcylated chromatin-associated proteins regulate transcription of metabolic and aging-related genes (52). The identification of H3T32Glc provides a specific epigenetic marker for future studies in insulin signaling and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Pho antibody was described earlier (32). After chromatin purification, Pho, O-GlcNAc, and RNA Pol II Ser2P ChIP-chip was performed by a minor modification of the method described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…O-GlcNAc was first detected on Drosophila polytene chromosomes (18) and later found at the promoter regions of Caenorhabditis elegans genes that are involved in a wide variety of pathways ranging from metabolism to aging (19). In addition to its role in Pc repression, OGT is thought to have additional roles in epigenetic regulation in mammals.…”
mentioning
confidence: 99%
“…Recent data suggests that O-GlcNAc is one component of the cellular stress response that is relevant to a variety of models of injury in several cell and tissue types. OGlcNAc levels become elevated in response to numerous forms of cell stress and tissue injury including: heat stress (Sohn et al 2004;Zachara et al 2004b), oxidative stress Zachara et al 2004b), ethanolic stress (Zachara et al 2004b;Ngoh et al 2009b), genotoxic stress (doxorubicin, belocin, and UVB irradiation; Zachara et al 2004bZachara et al , 2011aLove et al 2010), reductive stress (iodoacetamide; Zachara et al 2004b), ER stress (dithiothreitol and tunicamycin; Zachara et al 2004b;Ngoh et al 2009b), hypoxia reoxygenation (Ngoh et al 2009a;Ngoh et al 2008;Ngoh et al 2011), osmotic stress (NaCl, sorbitol, and sucrose; Zachara et al 2004b;Zou et al 2007), ATP depletion (sodium arsenite; Zachara et al 2004b), ischemia reperfusion injury (Champattanachai et al 2007(Champattanachai et al , 2008Fulop et al 2007a, b;Hwang et al 2010;Jones et al 2008;Laczy et al 2010;Liu et al 2006Liu et al , 2007Nagy et al 2006;Ngoh et al 2008Ngoh et al , 2009aNgoh et al , b, 2011Pang et al 2002;Zou et al 2009), and trauma hemorrhage Yang et al 2006a;Zou et al 2007Zou et al , 2009). This response occurs in primary and transformed cells, as well as in tissues in vivo and ex vivo.…”
Section: O-glcnac and The Cellular Stress Responsementioning
confidence: 99%